Hubungan Keragaman Gen Insuline-like Growth Factor 2 (IGF2) terhadap Sifat Pertumbuhan pada Ayam Kampung - Rahmadani, R. P.; Sumantri, C.; Darwati, S.; Ulupi, N. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2015)
Kampung chicken is one of Indonesia native chickens which has slow growth and it needs to be improved. Growth is a quantitative trait which is controled by many genes. One of the genes which plays a crucial role in controling growth is IGF2 gene. The objective of this study was to analyze the association of IGF2 gene polymorphisms with growth traits in kampung chicken. A total of 56 male and female chicks were maintained for 16 weeks and genotyped using PCR-RFLP method.Result showed there was TC muation on IGF2 gene and it was polymorphic in kampung chicken. Frequency of heterozigous TCwas the highest than the others. There was no association between IGF2 gene polymorphismswith growth traits in kampung chicken. It can be caused by the synonimus mutation on IGF2 sequence that does not alter the amino acid. Bot of the nucleotides coded for histidine. It may not give different effect toward the growth traits in kampung chicken.Keywords: growth traits, IGF2 gene, kampung chicken, polymorphisms